Single-cell RNA sequencing reveals the communications between tumor microenvironment components and tumor metastasis in osteosarcoma - Li, Jiatong; Bai, Yang; Zhang, He; Chen, Ting; Shang, Guanning (Frontiers in Immunology, 2024)
Introduction: Osteosarcoma is a common type of bone cancer characterized by a poor prognosis due to its metastatic nature. The tumor microenvironment (TME) plays a critical role in tumor metastasis and therapy response. Therefore, our study aims to explore the metastatic mechanism of osteosarcoma, potentially opening new avenues for cancer treatment. Methods: In this study, we collected data from the GSE152048, GSE14359, and GSE49003 datasets. Differentially expressed genes (DEGs) were identified in osteosarcoma cases with primary and metastatic features by R software and limma package. Gene ontology (GO) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analyses were performed to investigate metastasis-related genes. A protein-protein interaction (PPI) network was established using the STRING database to further analyze these metastasis-associated genes. The abundances of different cell types with a mixed cell population were estimated using the CIBERSORT approach. The scRNA-seq data were analyzed by the Seurat package in R software, and intercellular communications were elucidated using the CellChat R package. Results: In this study, 92 DEGs related to metastasis were identified, including 41 upregulated and 51 downregulated genes in both the GSE14359 and GSE49003 datasets. Metastasis-associated pathways were identified, including those involving the cyclin-dependent protein kinase holoenzyme complex, transferase complex, transferring phosphorus-containing groups, SCF ubiquitin ligase complex, and the serine/threonine protein kinase complex. KEGG and PPI network analyses revealed 15 hub genes, including Skp2, KIF20A, CCNF, TROAP, PHB, CKS1B, MCM3, CCNA2, TRIP13, CENPM, Hsp90AB1, JUN, CKS2, TK1 and KIF4A. Skp2 has been known as an E3 ubiquitin ligase involved in osteosarcoma progression. The proportion of CD8+ T cells was found to be higher in metastatic osteosarcoma tissues, and high expression of PHB was associated with a favorable prognosis in osteosarcoma patients. Additionally, 23 cell clusters were classified into 8 cell types, including chondrocytes, MSC, T cells, monocyte, tissue stem cells, neurons, endothelial cells, and macrophage. The 15 hub genes were expressed across various cell types, and interactions between different cell types were observed. Conclusion: Our study reveals the intricate communications between tumor microenvironment components and tumor metastasis in osteosarcoma.